2004
DOI: 10.1094/cchem.2004.81.3.314
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sorghum Cultivar on Injera Quality

Abstract: Injera is an Ethiopian flat bread made from cereals, with tef preferred for the best quality injera. Because sorghum is less expensive in Ethiopia, there is great interest in improving the quality of sorghum injera. Effects of cultivar on injera quality were studied using 12 Ethiopian sorghum cultivars of varying kernel characteristics. White tef with good injera making quality was included as a reference. Injera quality was evaluated using two techniques: descriptive sensory analysis of fresh injera and instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
88
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(98 citation statements)
references
References 5 publications
8
88
0
2
Order By: Relevance
“…Sometimes the flour is also used for making porridge, kitta (unleavened bread), and atmit or muk (gruel) (Selinus 1971). Various studies (Yetneberk et al 2004;Zegeye 1997) showed that in its injera making and keeping quality features, teff grain appeared superior among other cereal grains because of its high resistance to staling. During the baking of injera, starch is completely gelatinized to form a steam-leavened, spongy matrix, in which fragments of bran, embryo, microorganisms and organelles are embedded (Bultosa et al 2002;Parker et al 1989).…”
Section: Teff Utilizationmentioning
confidence: 99%
See 4 more Smart Citations
“…Sometimes the flour is also used for making porridge, kitta (unleavened bread), and atmit or muk (gruel) (Selinus 1971). Various studies (Yetneberk et al 2004;Zegeye 1997) showed that in its injera making and keeping quality features, teff grain appeared superior among other cereal grains because of its high resistance to staling. During the baking of injera, starch is completely gelatinized to form a steam-leavened, spongy matrix, in which fragments of bran, embryo, microorganisms and organelles are embedded (Bultosa et al 2002;Parker et al 1989).…”
Section: Teff Utilizationmentioning
confidence: 99%
“…During the baking of injera, starch is completely gelatinized to form a steam-leavened, spongy matrix, in which fragments of bran, embryo, microorganisms and organelles are embedded (Bultosa et al 2002;Parker et al 1989). Yetneberk et al (2004) studied the staling properties of injera prepared from teff and 12 varieties of sorghum. They reported that injera prepared from teff grain is resistant to staling and the maximum force required for bending fresh teff-injera and injera stored for 24 and 48 h is lower than that of sorghum-injera.…”
Section: Teff Utilizationmentioning
confidence: 99%
See 3 more Smart Citations